Searches for SUSY at the LHC - Obikhod, T.V. (Вопросы атомной науки и техники, 2014)
Searches for SUSY with R-parity conservation are connected with LSP particle - the best dark matter candidate. Using the new Minimal Supersymmetric Standard Model (MSSM) parameters received from recent experimental data at the LHC (CMS) it is possible to calculate the mass spectrum, partial width and production cross sections of superpatners. In the context of MSSM model histograms of mass distributions for superpartners ~qR and ~g are constructed.